2019
DOI: 10.1128/aac.01266-19
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated mcr-1 Colistin Resistance in Escherichia coli from a Black Kite in Russia

Abstract: The gene mcr-1 conferring resistance to last-line antibiotic colistin has been reported globally. Here, we describe the first detection of plasmid-mediated colistin resistance in Russian wildlife, an isolate of Escherichia coli sequence type 2280 from a black kite (Milvus migrans) scavenging raptor. Whole-genome sequencing and plasmid transferability experiments revealed that mcr-1.1 was located on conjugative IncI2 plasmid pDR164 (59891 bp). Migratory black kites may contribute to the global spread of mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 17 publications
1
28
0
5
Order By: Relevance
“…Acquisition of these genes is probably through foraging of feed at the landfill. Several studies have reported the presence of mcr-1 in migratory birds (Liakopoulos et al, 2016;Mohsin et al, 2016;Ruzauskas and Vaskeviciute, 2016;Tarabai et al, 2019), including co-resistance to colistin and cephalosporins. In fact, three of our isolates of white stork origin contained mcr-1 and bla CMY−2 genes within the same host.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of these genes is probably through foraging of feed at the landfill. Several studies have reported the presence of mcr-1 in migratory birds (Liakopoulos et al, 2016;Mohsin et al, 2016;Ruzauskas and Vaskeviciute, 2016;Tarabai et al, 2019), including co-resistance to colistin and cephalosporins. In fact, three of our isolates of white stork origin contained mcr-1 and bla CMY−2 genes within the same host.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, investigations on AMR in wild birds sometimes revealed unexpected reservoirs, such as recently where a high proportion of CP-resistant NDM-5-producing Klebsiella pneumoniae was observed in migratory birds in China ( Liao et al, 2019 ). With regard to colistin resistance, a limited number of studies reported the plasmid-mediated mcr-1 gene in wild birds ( Tarabai et al, 2019 ). In France, ESBL-producing Enterobacteriaceae were detected in 2009 in 17/90 (18.9%) of juvenile yellow-legged gulls ( Bonnedahl et al, 2009 ), while the sporadic detection of a VIM-1-producing E. coli was reported in 2012 in the same area (South of France) and the same bird species ( Vittecoq et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies were also based on fecal dejections collected in various places where birds live or transit, such as landfills, beaches, urban parks, nests, and other habitats, but associating fecal samples to the right bird species may be challenging. In some situations however, these approaches valuably allowed studying AMR in large cohorts of individuals of the same bird species in their natural environment, as for instance illustrated for black kites ( Milvus milvus ), corvids ( Corvus brachyrhynchos , Corvus corax ), gulls ( Larus glaucescens, Larus ridibundus ), pigeons ( Columba livia ) or storks ( Ciconia ciconia ) ( Bonnedahl et al, 2010 , 2014 ; Jamborova et al, 2018 ; Tarabai et al, 2019 ; Zendri et al, 2020 ). Here, we adopted a different strategy by systematically sampling all incoming wild birds at a French rescue center over a 6-month period.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the fact that until the first report of mcr-1 gene, colistin resistance in Enterobacteriaceae was believed to be chromosomally mediated 36 . However, since 2016, the mcr-1 gene was reported in Enterobacteriaceae recovered from food, animals, and human specimens in China, and it has subsequently been reported worldwide 11, [48][49][50][51][52][53] . The wide spread of the mcr-1 dramatically challenges the newly renewed interest in colistin for clinical use and opens a new research topic on colistin.…”
Section: Discussionmentioning
confidence: 99%